2002
DOI: 10.1177/0148607102026002130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glycine on intestinal ischemia‐reperfusion injury

Abstract: Local perfusion with 20% glycine can diminish warm ischemia-reperfusion injury to the rat small intestine in an in vivo model. The role of glycine supplementation should be evaluated in situations where hemodynamic instability may be responsible for breakdown in the gut barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
27
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
(29 reference statements)
4
27
0
3
Order By: Relevance
“…32) Glycine is an immunomodulatury agent, inhibits macrophage activation, reduces inflammation and inhibits apoptosis. 33) In the intestine, glycine limits the damage caused by intestinal reperfusion injury, [34][35][36][37][38][39] abdominal irradiation 40) and can prevent or reduce the severity of experimentally induced colitis. 41) As in other tissues, the protection appears to be at least bi-modal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32) Glycine is an immunomodulatury agent, inhibits macrophage activation, reduces inflammation and inhibits apoptosis. 33) In the intestine, glycine limits the damage caused by intestinal reperfusion injury, [34][35][36][37][38][39] abdominal irradiation 40) and can prevent or reduce the severity of experimentally induced colitis. 41) As in other tissues, the protection appears to be at least bi-modal.…”
Section: Introductionmentioning
confidence: 99%
“…41) As in other tissues, the protection appears to be at least bi-modal. Tsune et al 41) demonstrated that dietary glycine was able to reduce intestinal inflammation in rats when given 2 d after administration of the damaging agent trinitrobenzenesulphonic acid (TNBS), whereas the work of Lee et al 37) showed a necessity for glycine administration before reperfusion to prevent ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Such was the case of: glucagon 13 , 21-amino-steroids 14 , pentoxifylline 15 , somatostatin 16 and perfluorocarbons 17 . More recently, by using a model of HR in rats, glycine was put to the test as a protective agent of intestinal injuries stemming there from [18][19][20] . Glycine is a non-essential simple amino acid formed by a carbon molecule bonded to an amino group and to a carboxyl group.…”
mentioning
confidence: 99%
“…Glycine is a non-essential amino acid that protects the gut against lesions caused by the ischemia-reperfusion phenomenon [18][19][20]28 . It is considered an anti-inflammatory, immune modulator agent of direct cytoprotective function 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation